2023
DOI: 10.21037/tcr-22-2192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immune checkpoint inhibitors (ICIs) combined with antiangiogenic therapy for thymic epithelial tumors (TETs): a retrospective study

Abstract: Background: Immune checkpoint inhibitors (ICIs) combined with antiangiogenic therapy have shown promising antitumor activity against a range of advanced cancers. However, evidence is lacking as to whether this combination therapy could benefit thymic epithelial tumors (TETs). We aimed to explore the efficacy and safety of this combination therapy in advanced TETs.Methods: Ten patients with pathologically proven advanced TETs who received ICIs combined with an antiangiogenic agent from 2020 to 2022 at Zhejiang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 37 Our team has performed a retrospective study using 10 patients with thymic epithelial tumors receiving immunotherapy combined with antiangiogenic therapy. 38 The results showed promising antitumor activity and a PFS of 6.7 months. 38 Similarly, the present study demonstrated a PFS of 6.8 months for immunotherapy combined with antiangiogenic therapy in the latter-line therapy group of advanced thymic carcinoma patients with liver metastases.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 37 Our team has performed a retrospective study using 10 patients with thymic epithelial tumors receiving immunotherapy combined with antiangiogenic therapy. 38 The results showed promising antitumor activity and a PFS of 6.7 months. 38 Similarly, the present study demonstrated a PFS of 6.8 months for immunotherapy combined with antiangiogenic therapy in the latter-line therapy group of advanced thymic carcinoma patients with liver metastases.…”
Section: Discussionmentioning
confidence: 90%
“… 38 The results showed promising antitumor activity and a PFS of 6.7 months. 38 Similarly, the present study demonstrated a PFS of 6.8 months for immunotherapy combined with antiangiogenic therapy in the latter-line therapy group of advanced thymic carcinoma patients with liver metastases. Although advanced thymic carcinoma patients with liver metastases showed poor immunotherapy efficacy, the combination therapy with antiangiogenic therapy may still present a new opportunity for the latter-line therapy group patients with liver metastases.…”
Section: Discussionmentioning
confidence: 90%